An Analysis of Racial Discriminations as Seen in Kathryn Stokett’s Novel The Help - Nazara, Marleni Zairanis; Reni, Fetri (Jurnal Ilmiah Langue and Parole, 2019)
The problem in this analysis is the existence of black racial discrimination by white people who consider themselves more powerful than the black race. This is illustrated in the novel The Help through the treatment of white employers against their helpers, the black race. In this analysis, the author wants to analyze discriminatory actions, causes and effects of racial discrimination in the novel The HelpIn this analysis, descriptive research is taken as a method of data collection. As for the method of data analysis, the authors conducted qualitative methods with understanding the novel. Data collection techniques use qualitative techniques by taking notes in collecting primary data. In data analysis techniques, the author uses structuralism method techniques by interpreting data.The results of this research are: 1) there are elements and acts of discrimination and segregation from white employers to black maids and also various racist actions towards other blacks described in the novel. 2) the cause of racial discriminations in this novel stems from Hilly's idea of making separate toilets with black maids 3) The effect of this racial discriminations is the publication of the novel The Help in Mississippi, the changing viewpoint of their employers and helpers and vice versa.